2022
DOI: 10.1111/jomf.12866
|View full text |Cite|
|
Sign up to set email alerts
|

“You're biracial but…”: Multiracial socialization discourse among mommy bloggers with Black and non‐Black multiracial children

Abstract: Objective This study examines thematic content and discourse surrounding multiracial socialization between Black and non‐Black multiracial families on multiracial mommy blogs. Background Mommy blogs have been recognized as a medium through which mothers challenge dominant representations of motherhood, create community with other mothers, and seek out advice. But little is known about how mothers write about and discuss race, racism, and multiracial socialization online. This study addresses this knowledge gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Although the magnitude of how blogs contribute to popular parenting culture and impact individual readers is contested, blog posts still provide an important lens into some of the most common, pressing, and widely discussed family issues today. As Reyna (2022) explained, “reflections and recounts of microlevel family dynamics have the capacity to contribute to and shape macrolevel cultural production” (p. 1525). Our microsociological approach therefore considers how “big” parenting concerns can be seen and examined through “small” digital narratives (Stolte et al, 2001).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the magnitude of how blogs contribute to popular parenting culture and impact individual readers is contested, blog posts still provide an important lens into some of the most common, pressing, and widely discussed family issues today. As Reyna (2022) explained, “reflections and recounts of microlevel family dynamics have the capacity to contribute to and shape macrolevel cultural production” (p. 1525). Our microsociological approach therefore considers how “big” parenting concerns can be seen and examined through “small” digital narratives (Stolte et al, 2001).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It would be fruitful for sociologists and family scientists to take a critical intersectional lens to unpack variation in parenting blogs by race, class, sexuality, and marital status. Recent work has found that blog discourse about parental burdens and children's socialization and well‐being can vary in notable ways based on race/ethnicity (Reyna, 2022). Second, because our analysis gave primacy to our qualitative findings, there is a need for comparative quantitative research on parenting blogs.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation